THE ANALYSIS OF LILY BLOOM’S TRAUMA IN COLLEEN HOOVER’S IT ENDS WITH US - G. Sarungu, Lidya; Andayani, Ambar (TANDA, 2023)
This analysis presents the emotional feeling found in Colleen Hoover’s It Ends with Us especially in the main character, Lily Bloom. The findings show that Lily Bloom’s way of coping with her trauma is learned from her experience during her teenage years and adult life. In this analysis, the writer focuses on Lily Bloom’s trauma as well in analysis of causes and effects of her trauma and her specific coping-mechanism. The writer uses a psychological approach to analyze the main character's trauma by using the theories of Cathy Caruth, Judith Herman and James Pennebaker. The analysis shows that Lily’s trauma reflected in the novel is when she finds comfort in shuffling cards and when she has hallucinations. The causes of trauma is the abusive cycle that her father does to her mother when she is a teenager. Lily Bloom's experiences with traumatic events have negative and positive effects. The negative effects include difficulties in relationships, self-conflict, and being affected by feelings. The positive effect is that she has finally realized, by looking at her life possibilities that she wants to explore things to make them better. She uses expressive writing as a specific coping mechanism to learn about her trauma.